Ferrocene-containing liquid crystal polymer monomer, polymer and application thereof
By introducing the long -chain alkyl -side chain in the liquid crystal polymer and the use of RAFT aggregation reactions, the problem of simple structure and poor functionality of the existing technology containing Ermao Iron LCD polymers, realizing high -performance LCD polymer polymers Preparation has good mechanical properties, thermal stability and liquid crystal properties.
Patent Information
- Application Number
- CN202411503989.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In the prior art, the ferrocene-containing crust-type liquid crystal polymer has a simple structure and poor functionality, making it difficult to meet the needs of high-performance materials.
By introducing the long -chain alkyl -side chain, prepare the LCD polymer monomer and polymer containing Ermao Iron with more complex structures and rich functions, and use RAFT aggregation reactions and specific esterization reactions to improve their mechanical performance, heat stability Nature and liquid crystal properties.
The high -performance membrane, good liquid crystal and electrochemical properties of LCD polymers are realized, and the application scope of its application in high -performance materials is expanded.
Smart Images

Figure CN119371465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to liquid crystal polymer materials, in particular to a liquid crystal polymer monomer and polymer containing ferrocene and uses thereof. Background Art
[0002] There can be a variety of functional groups on the side chains of existing chitosan-type liquid crystal polymers, such as triphenylene, oligomeric silsesquioxane, cholesterol, rod-shaped molecules containing biphenyl structures, etc. By adding functional groups, the formation of polymer liquid crystallinity can be affected, and new functions including photoelectric response, fluorescence or conductivity can be imparted.
[0003] Ferrocene can be used to prepare multifunctional materials, such as conductive materials, magnetic ceramic precursors, and high refractive index materials, due to its electron-rich structure. In addition, it has a wide range of applications in catalysis, drug delivery, and electrochemistry. Since ferrocene units are prone to losing electrons and undergoing redox reactions, they can be used to transport charges. In early studies, it was found that the charge transfer rate in liquid crystal films containing ferrocene is more than 1,000 times higher than that in solution, which greatly reduces the reaction activation energy in the electrochemical catalytic process.
[0004] Some studies have reported the use of ferrocene groups and simple esterification reactions to prepare ferrocene-containing polymers, but their structures are simple and their functions are limited. The present invention provides a new ferrocene-containing liquid crystal polymer monomer and polymer, which has a more complex structure and richer functions. Summary of the invention
[0005] The purpose of the present invention is to provide a liquid crystal polymer monomer and polymer containing ferrocene and a preparation method thereof, which aims to solve the problems of simple structure and poor functionality of the shell-type liquid crystal polymer containing ferrocene in the prior art. By introducing long-chain alkyl side chains, the obtained polymer has better mechanical properties, thermal stability and liquid crystal properties, and its application range in the field of high-performance materials is expanded.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A liquid crystal polymer monomer containing ferrocene, the structure of which is shown in Formula 1:
[0008]
[0009] wherein n is an integer ≥ 1, and R includes a C2-C6 alkenyl group.
[0010] Furthermore, n is an integer of 6-20.
[0011] Furthermore, n is an integer of 6-12, and R is a C2-C3 alkenyl group.
[0012] Furthermore, n is 6, and R is vinyl.
[0013] The method for preparing the above-mentioned ferrocene-containing liquid crystal polymer monomer comprises the following steps:
[0014] Introducing a hydroxyl protecting group into n-bromo-1-n-alkanol, and then reacting with C2-C6 alkenyl terephthalic acid to obtain a C2-C6 alkenyl terephthalic acid derivative;
[0015] Removing the hydroxyl protecting group from the C2-C6 alkenyl terephthalic acid derivative, and then carrying out an esterification reaction with ferrocenecarboxylic acid to obtain a liquid crystal polymer monomer containing ferrocene;
[0016] The n-bromo-1-n-alkanols include: 6-bromo-1-hexanol, 16-bromo-1-hexadecanol, and 20-bromo-1-eicosanol.
[0017] Furthermore, the protecting group is tert-butyldimethylsilyl; when the hydroxy protecting group is introduced, the catalyst is Et 3 N and DMAP.
[0018] Furthermore, after the hydroxyl protecting group is introduced into n-bromo-1-n-alkanol, it is reacted with vinyl terephthalic acid, the water absorbent is EDCI, and the catalyst is DMAP.
[0019] Furthermore, in the reaction of removing the protecting agent group of the C2-C6 alkenyl terephthalic acid derivative and then carrying out an esterification reaction with ferrocenecarboxylic acid, the water absorbent is EDCI and the catalyst is DMAP.
[0020] The present invention also protects a liquid crystal high molecular polymer, the polymer structure of which is shown in Formula 2:
[0021]
[0022] Wherein m represents the degree of polymerization, m is an integer of 10-500, and n is an integer of 6-20.
[0023] Furthermore, m is 50 or 100, and n is 6.
[0024] The method for preparing the above-mentioned liquid crystal polymer comprises the following steps:
[0025] The liquid crystal polymer monomers are subjected to RAFT polymerization reaction to obtain the final liquid crystal polymer. The RAFT reagent used in the RAFT polymerization reaction includes: dithiodialkyl dithiophosphate and alkyl sulfate.
[0026] Furthermore, in the polymer obtained by the above method for preparing the liquid crystal polymer, R is a vinyl group.
[0027] The present invention also protects a liquid crystal material, which includes the above-mentioned liquid crystal high molecular polymer.
[0028] The present invention also protects a battery, which comprises the above-mentioned liquid crystal material.
[0029] The present invention also provides a method for synthesizing a liquid crystal high molecular polymer containing ferrocene, and the specific process is as follows:
[0030]
[0031] In the above process, n-bromo-1-n-alkanol and TBSCL were reacted for 2 h to introduce TBS protecting group, and the reaction catalyst was Et 3 N and DMAP;
[0032] The n-bromo-1-n-alkanol after the introduction of TBS protective group was reacted with vinyl terephthalic acid for 24 hours to obtain a vinyl terephthalic acid derivative, the catalyst was DMAP, and the water absorbent was EDCI;
[0033] Vinyl terephthalic acid derivatives were reacted with CH 3 CN / H 2 O and HF / THF mixed reaction, remove TBS protective group, to obtain the vinyl terephthalic acid derivative without protective group;
[0034] The vinyl terephthalic acid derivative with the protective group removed is subjected to an esterification reaction with ferrocenecarboxylic acid for 24 hours to obtain a liquid crystal polymer monomer containing ferrocene, the catalyst is DMAP, and the water absorbent is EDCI;
[0035] The ferrocene-containing liquid crystal polymer monomer is polymerized by RAFT to obtain the ferrocene-containing liquid crystal polymer.
[0036] Beneficial effects of the present invention: The liquid crystal high molecular polymer containing ferrocene obtained by the present invention has completely polymerized monomers and has excellent liquid crystal properties and electrochemical properties.
[0037] The invention introduces a long alkyl chain to make the ferrocene unit have better mobility, promote the orderly arrangement of the molecular units, and have good liquid crystal properties and electrochemical properties.
[0038] The liquid crystal macromolecular polymer prepared by the invention has good film-forming property and is convenient for processing and application.
[0039] The ferrocene-containing liquid crystal high molecular polymer obtained by the invention also has good thermal stability.
[0040] The preparation method of the invention is used to prepare a liquid crystal high molecular polymer containing ferrocene, which has high conversion rate and good dispersion rate and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 : is the SAXS graph of the ferrocene-containing liquid crystal polymer obtained in Example 2;
[0043] Figure 2 : is a cyclic voltammogram of the ferrocene-containing liquid crystal polymer obtained in Example 1;
[0044] Figure 3 : Figure 3 (a) is the oxidation current V of the ferrocene-containing liquid crystal polymer obtained in Example 1 1 / 2 The change relationship diagram of Figure 3 (b) is the reduction current V of the ferrocene-containing liquid crystal polymer obtained in Example 1 1 / 2 The change relationship diagram of
[0045] Figure 4 : is a cyclic voltammogram of the ferrocene-containing liquid crystal polymer obtained in Example 2;
[0046] Figure 5 : Figure 5 (a) is the oxidation current V of the ferrocene-containing liquid crystal polymer obtained in Example 2 1 / 2 The change relationship diagram of Figure 5 (b) is the reduction current V of the ferrocene-containing liquid crystal polymer obtained in Example 2 1 / 2 The change relationship diagram of
[0047] Figure 6 : SAXS graph of the ferrocene-containing polymer obtained in Comparative Example 1-2. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Example 1
[0050] Preparation of Liquid Crystalline Polymers Containing Ferrocene
[0051] S1, 6-bromo-1-hexanol (0.2 mol) was reacted with TBSCL (0.25 mol) to introduce TBS protecting group, and the catalyst was Et 3 N (0.1 mL) and DMAP (0.1 mol) were added and reacted for 2 h;
[0052] S2, adding a water absorbent and a catalyst to 6-bromo-1-hexanol (0.5 mol) after the introduction of TBS protecting group and vinyl phthalic acid (0.23 mol) to react to obtain a vinyl terephthalic acid derivative, wherein the water absorbent is EDCI (1 mol) and the catalyst is DMAP (0.1 mol), and the reaction is carried out for 24 hours;
[0053] S3, vinyl terephthalic acid derivatives and CH 3 CN / H 2 O(CH 3 CN and H 2 O volume ratio of 3:1) and HF / THF (HF and THF volume ratio of 1:1) mixed reaction, remove TBS protecting group, to obtain the vinyl terephthalic acid derivative without protecting group;
[0054] S4, subjecting the vinyl terephthalic acid derivative obtained in step S3 and removing the protecting group to an esterification reaction with ferrocenecarboxylic acid for 24 hours to obtain a liquid crystal polymer monomer containing ferrocene, wherein the catalyst is DMAP and the water absorbent is EDCI;
[0055] The structural formula of the liquid crystal polymer monomer containing ferrocene is:
[0056]
[0057] The ferrocene-containing liquid crystal polymer monomer obtained in step S4 is subjected to RAFT polymerization reaction to obtain a final liquid crystal polymer polymer, the RAFT agent used in the RAFT polymerization reaction is dithiodialkyl dithiophosphate, the molar ratio of dithiodialkyl dithiophosphate to the ferrocene-containing liquid crystal polymer monomer is 1:50, and a liquid crystal polymer polymer (P50) is obtained.
[0058] The structural formula of the liquid crystal polymer (P50) is:
[0059]
[0060] Example 2
[0061] Preparation of liquid crystal polymer containing ferrocene:
[0062] The ferrocene-containing liquid crystal polymer monomer obtained in Example 1 was subjected to RAFT polymerization reaction to obtain a final liquid crystal polymer polymer. The RAFT agent used in the RAFT polymerization reaction was dithiodialkyl dithiophosphate, and the molar ratio of dithiodialkyl dithiophosphate to the ferrocene-containing liquid crystal polymer monomer was 1:100 to obtain a liquid crystal polymer (P100).
[0063] The structural formula of liquid crystal polymer (P100) is:
[0064]
[0065] Example 3
[0066] Preparation of liquid crystal polymer containing ferrocene:
[0067] S1. 20-bromo-1-eicosanol (0.2 mol) and TBSCL (0.25 mol) were stirred in Et 3 The reaction was carried out in the presence of N (0.1 mL) and DMAP (0.1 mol) to introduce the TBS protecting group. The catalyst was Et 3 N and DMAP, the solvent was DCM;
[0068] S2, reacting 20-bromo-1-eicosanol (0.5 mol) after the introduction of TBS protecting group with vinyl terephthalic acid (0.23 mol) to obtain a vinyl terephthalic acid derivative, wherein the water absorbent is EDCI (1 mol) and the catalyst is DMAP (0.1 mol);
[0069] S3, vinyl terephthalic acid derivatives in CH 3 CN / H 2 O (volume ratio of 3:1) and HF / THF (volume ratio of 1:1) to remove the TBS protecting group, and then react with ferrocenecarboxylic acid to obtain a liquid crystal polymer monomer containing ferrocene, wherein the water absorbent is EDCI and the catalyst is DMAP;
[0070] S4, subjecting the ferrocene-containing liquid crystal polymer monomer obtained in step S3 to RAFT polymerization reaction to obtain a final liquid crystal polymer, wherein the RAFT agent used in the RAFT polymerization reaction is dithiodialkyl dithiophosphate to obtain a liquid crystal polymer, and the molar ratio of dithiodialkyl dithiophosphate to the ferrocene-containing liquid crystal polymer monomer is 1:500.
[0071] Example 4
[0072] Preparation of liquid crystal polymer containing ferrocene:
[0073] S1. 16-bromo-1-hexadecanol (0.2 mol) and TBSCL (0.25 mol) were stirred in Et 3 The reaction was carried out in the presence of N (0.1 mL) and DMAP (0.1 mol) to introduce the TBS protecting group. The catalyst was Et 3 N and DMAP, the solvent was DCM;
[0074] S2, reacting 16-bromo-1-hexadecanol (0.5 mol) after the introduction of TBS protecting group with vinyl terephthalic acid (0.23 mol) to obtain a vinyl terephthalic acid derivative, wherein the water absorbent is EDCI (1 mol) and the catalyst is DMAP (0.1 mol);
[0075] S3, vinyl terephthalic acid derivatives in CH 3 CN / H 2 O (volume ratio of 3:1) and HF / THF (volume ratio of 1:1) to remove the TBS protecting group, and then react with ferrocenecarboxylic acid to obtain a liquid crystal polymer monomer containing ferrocene, wherein the water absorbent is EDCI and the catalyst is DMAP;
[0076] S4, subjecting the ferrocene-containing liquid crystal polymer monomer obtained in step S3 to RAFT polymerization to obtain a final liquid crystal polymer, wherein the RAFT agent used in the RAFT polymerization reaction is dithiodialkyl dithiophosphate to obtain a liquid crystal polymer, and the molar ratio of dithiodialkyl dithiophosphate to the ferrocene-containing liquid crystal polymer monomer is 1:10.
[0077] Comparative Example 1
[0078] Comparative Example 1 is a high molecular polymer containing bornene;
[0079] The corresponding polymer structure is:
[0080]
[0081] Comparative Example 2
[0082] Comparative Example 2 is a high molecular polymer containing bornene;
[0083] The structure of high molecular polymer is:
[0084]
[0085] The structural formula of the polymer monomer used to prepare the polymers of Comparative Example 1 and Comparative Example 2 is as follows:
[0086]
[0087] The liquid crystal polymer of ferrocene obtained in Example 1-2 was tested:
[0088] The thermal properties of the polymer were characterized by TGA (thermogravimetric analysis) and DSC (differential scanning calorimetry) to obtain the 5% decomposition temperature and glass transition temperature. In Example 1, the 5% decomposition temperature of the polymer was 349°C and the glass transition temperature was 82°C. In Example 2, the 5% decomposition temperature of the polymer was 353°C and the glass transition temperature was 84°C. Both had good thermal stability.
[0089] Depend on Figure 1 It can be seen from the SAXS curve of the ferrocene-containing liquid crystal polymer obtained in Example 2 that Figure 1 It can be seen that it has good liquid crystal properties.
[0090] Depend on Figure 2-5 The cyclic voltammetry curve and current V of the liquid crystal polymer containing ferrocene in Example 1-2 are shown in FIG. 1 / 2 The change relationship diagram of Figure 3 (a) is the oxidation current V of the ferrocene-containing liquid crystal polymer obtained in Example 1 1 / 2 The change relationship diagram of Figure 3 (b) is the reduction current V of the ferrocene-containing liquid crystal polymer obtained in Example 1 1 / 2 The change relationship diagram of Figure 5 (a) is the oxidation current V of the ferrocene-containing liquid crystal polymer obtained in Example 2 1 / 2 The change relationship diagram of Figure 5 (b) is the reduction current V of the ferrocene-containing liquid crystal polymer obtained in Example 2 1 / 2 The change relationship diagram of
[0091] The solvent used in the test was dichloromethane, the electrolyte was tetrabutylammonium hexafluorophosphate, the reference electrode was Ag, the working electrode was a glassy carbon electrode, and the counter electrode was Pt. The cyclic voltammetry (CV) curves at different scan rates were tested respectively.
[0092] The redox peak potential Epi(V) of the two polymers at different scan rates is relatively stable. With the increase of scan rate, the peak-to-peak potential difference AEp(V) gradually increases, which is mainly due to the ohmic drop of the solution after the scan rate increases. For P50, at low scan rate, its peak-to-peak potential difference AEp(V) is 64mV (10mV / s), which is close to the theoretical value of the reversible redox process, but the ratio of oxidation current to reduction current i / ie at this time is less than the theoretical value of 1. Therefore, at low scan rate, the redox process is irreversible. With the increase of scan rate, ip / i~ gradually increases and approaches 1, but it is still irreversible. For polymer P100, at low scan rate, its peak-to-peak potential difference ΔEp(V) is 39mV (25mV / s), which is significantly less than the theoretical value of 59mV of the reversible redox process, indicating that adsorption may have occurred on the electrode surface and the redox process is irreversible.
[0093] Depend on Figure 2 and Figure 3 It can be seen that the current of the polymer P50 obtained in Example 1 is proportional to the half of the scan rate, indicating that the electrode process is diffusion controlled. Figure 4 and Figure 5 It can be seen that the current of the polymer P100 obtained in Example 2 is proportional to the scan rate, indicating that the electrode process is adsorption controlled.
[0094] Figure 6 is the SAXS diagram of the ferrocene-containing polymer obtained in Comparative Example 1-2, Figure 6 It can be seen that no obvious diffraction peak appears, that is, the polymers obtained in Comparative Examples 1 and 2 have no liquid crystal properties, and ferrocene itself does not have the characteristic of orderly arrangement. In Comparative Examples 1-2, the ferrocene unit also destroys the liquid crystal structure of MILCP itself.
Claims
1. A liquid crystal polymer monomer containing ferrocene, characterized in that: The structure of the liquid crystal polymer monomer is shown in Formula 1: wherein n is an integer of 6-20, and R is a C2-C6 alkenyl group.
2. The liquid crystal polymer monomer according to claim 1, characterized in that ,, R is a C2-C3 alkenyl group, and n is an integer of 6-16.
3. The liquid crystal polymer monomer according to claim 1, characterized in that: R is vinyl and n is 6.
4. A method for preparing the ferrocene-containing liquid crystal polymer monomer according to any one of claims 1 to 3, comprising the following steps: Introducing a hydroxyl protecting group into n-bromo-1-n-alkanol, and then reacting with terephthalic acid containing an alkenyl group to obtain an alkenyl-containing terephthalic acid derivative; The hydroxyl protecting group in the alkenyl-containing terephthalic acid derivative is removed, and then the derivative is subjected to an esterification reaction with ferrocenecarboxylic acid to obtain a liquid crystal polymer monomer containing ferrocene.
5. The method according to claim 4, characterized in that The hydroxyl protecting group is tert-butyldimethylsilyl.
6. A liquid crystal polymer, characterized in that: The polymer structure is shown in Formula 2: Wherein m represents the degree of polymerization, m is an integer of 10-500, and n is an integer of 6-20.
7. The liquid crystal polymer according to claim 6, characterized in that: m is an integer of 50-100, and n is an integer of 6-16.
8. A method for preparing the liquid crystal polymer according to claim 6, comprising the following steps: The liquid crystal polymer monomer according to any one of claims 1 to 3 is subjected to RAFT polymerization to obtain the final liquid crystal polymer. The RAFT agent used in the RAFT polymerization reaction includes: dithiodialkyl dithiophosphate and alkyl sulfate.
9. A liquid crystal material, characterized in that: The liquid crystal material includes the liquid crystal polymer described in claims 6-7 or the liquid crystal polymer obtained by the method described in claim 8.
10. A battery, characterized in that: The battery comprises the liquid crystal material of claim 9.
Citation Information
Patent Citations
Preparation method of rigid chain liquid crystal polymer material for hydrogen peroxide sensors
CN105153340A
Benzoate monomer containing ferrocene unit and preparation method thereof
CN114702533A
Magnetic polymer, high-impact-strength magnetic ABS composite material prepared from magnetic polymer and application of high-impact-strength magnetic ABS composite material
CN118459640A